Defective Monocyte Enzymatic Function and an Inhibitory Immune Phenotype in Human Immunodeficiency Virus-Exposed Uninfected African Infants in the Era of Antiretroviral Therapy . (11th April 2022) - Afran, Louise; Jambo, Kondwani C; Nedi, Wilfred; Miles, David J C; Kiran, Anmol; Banda, Dominic H; Kamg'ona, Ralph; Tembo, Dumizulu; Pachnio, Annette; Nastouli, Eleni; Ferne, Brigit; Mwandumba, Henry C; et al.
Abstract: Background: Human immunodeficiency virus-exposed uninfected (HEU) infants are a rapidly expanding population in sub-Saharan Africa and are highly susceptible to encapsulated bacterial disease in the first year of life. The mechanism of this increased risk is still poorly understood. We investigated whether human immunodeficiency virus (HIV)-exposure dysregulates HEU immunity, vaccine-antibody production, and human herpes virus amplify this effect. Methods: Thirty-four HIV-infected and 44 HIV-uninfected pregnant women were recruited into the birth cohort and observed up to 6 weeks of age; and then a subsequent 43 HIV-infected and 61 HIV-uninfected mother-infant pairs were recruited into a longitudinal infant cohort at either: 5–7 to 14–15; or 14–15 to 18–23 weeks of age. We compared monocyte function, innate and adaptive immune cell phenotype, and vaccine-induced antibody responses between HEU and HIV-unexposed uninfected (HU) infants. Results: We demonstrate (1) altered monocyte phagosomal function and B-cell subset homeostasis and (2) lower vaccine-induced anti- Haemophilus influenzae type b ( Hib) and anti-tetanus toxoid immunoglobulin G titers in HEU compared with HU infants. Human herpes virus infection was similar between HEU and HU infants. Conclusions: In the era of antiretroviral therapy-mediated viral suppression, HIV exposure may dysregulate monocyte and B-cell function, during the vulnerable period of immune maturation. This may contribute to the high rates of invasive bacterial disease and pneumonia in HEU infants. Abstract : Early life HIV exposure may dysregulate innate and adaptive immunity, specifically, monocyte function and vaccine-induced immunity to encapsulated bacteria. This may lead to altered protection and susceptibility to disease from encapsulated bacteria.